The Diagnostic Usefulness of Immunohistochemistry for Odontogenic Lesions - Hunter, Keith D.; Speight, Paul M. (Head & neck pathology (Totowa, N.J.), 2014)
The diagnosis of odontogenic tumors can be challenging, largely due to their rarity and consequent difficulties in gaining experience in their assessment. In most cases, careful attention to morphology, in conjunction with clinical and radiological features will allow a diagnosis to be made. However, in some cases, immunohistochemical analysis of the tumor may be useful. In this review we will outline the immunohistochemical expression profile of normal developing odontogenic tissues and a range of odontogenic tumors. In many cases the immunohistochemical markers are neither specific nor sensitive enough to be of help in diagnosis, but in some cases such analysis may prove very useful. Thus we have outlined a limited number of circumstances where immunohistochemistry may be of use to the practicing diagnostic pathologist.